Performance Evaluation of a Microcontroller-Based Automatic Fish Weighing System Using Load Cell Sensor - Dirja Nur Ilham; Muhammad Khoiruddin Harahap; Muhammed Saat Talib; Douglas pardede; Harmayani Harmayani (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid advancement of automation technology in the fisheries sector has increased the demand for efficient and accurate fish weight measurement systems. Conventional manual weighing methods are often time-consuming and prone to human error, particularly in high-volume environments. This study aims to evaluate the performance of a microcontroller-based automatic fish weighing system using a load cell sensor with real-time output. The proposed system integrates a load cell sensor with an HX711 amplifier module and an Arduino Uno microcontroller to measure fish weight and display results instantly via an LCD. The performance evaluation focuses on key parameters, including accuracy, measurement error, response time, and system stability. Experimental testing was conducted by comparing prototype measurements with a standard digital scale under various load conditions. The results indicate that the system achieves high accuracy exceeding 98%, with an average error below 2%. The response time ranges between 1–2 seconds, demonstrating the system’s capability for real-time applications. Additionally, the system exhibits good stability with minimal fluctuations in repeated measurements. These findings suggest that the proposed prototype is reliable and efficient for practical use in aquaculture and fish market environments. The system also supports digital transformation in fisheries through improved measurement accuracy, reduced human error, and enhanced operational efficiency.